Competing with information : a manager's guide to creating business value with information content - Marchand, Donald A. (John Wiley ChichesterGB, 2000)
Targets managers in presenting information i.e.information management, information systems, information technology etc., as a key resource in the search for competitive advantage. Identifies 4 areas in which managers can use information to create business value viz. adding value with customers and markets; creating new realities; minimising business risk; and reducing the cost of transactions and processes. Discusses how information can be used to achieve business results and explains how information management practices can be benchmarked, evaluated and transformed.